Perancangan dan Pengembangan Sistem In Out Stock PT Greentech Globalindo - Yefta Christian; Denissa Denissa (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Asset management is the act of calculating the number of assets going in and out per day according to customer requests. The flow of asset management must be recorded perfectly to create effectiveness and efficiency; therefore, a company must have a capable flow recording system. Using the RAD method to focus more on development stage, this project aims to design a website-based application to save time and increasing accuracy in calculating the amount of stock going in and out. By using Django, React and PostgreSQL, the author succeeded in designing a website-based in-out stock recording application to assist the stock calculation process at PT Greentech Globalindo. And thus, the company need not rely on manual reports and therefore accelerate up the inventory process, while getting some new features such as reporting and dashboard